20 years of exploitation of the Yarragadee aquifer in the Perth Basin of Western Australia for direct-use of geothermal heat. (September 2015) - Pujol, Martin; Ricard, Ludovic P.; Bolton, Grant
Highlights: An integrated study from resource characterisation to end-user. Above ground engineering of direct-use geothermal projects in Perth is presented. Direct-use geothermal projects in Perth have a 100% success rate. The success is associated with a favourable geothermal resource and adequate design. Scaling-up will require diversification of the direct-use applications. Electric power production will require characterisation of the deeper resources. Abstract: Aquifers in the Perth Metropolitan Region of Western Australia have been explored and exploited for water supply since the late 19th century. Throughout the early 20th century, the availability of warm groundwater from the Yarragadee confined aquifer at relatively shallow depths was popular with laundries, public baths and for industrial applications but it was not until 1997 that the first direct-use geothermal project for bathing and swimming was implemented. By 2016, a dozen commercially successful geothermal schemes will use low enthalpy geothermal water supplies from the Yarragadee aquifer at depths ranging from 750 to 1150 m for heating leisure centres, building air and outdoor pools. With distributed heat estimated to more than 110 × 10 3  GJ per year and up to 180 × 10 3  GJ when considering projects currently at construction stage but not yet commissioned, Perth currently has the biggest concentration of operating geothermal direct-use projects in Australia. The development of geothermal projects in Perth was made possible by early achievements pioneered by designers from the groundwater industry. This paper presents the hydrogeological setting of the Yarragadee aquifer which is the main geothermal resource in Perth, the well and surface heat exchanger design criteria, the economic and environmental considerations, and the best practices and circumstances that led to the 100% success rate of direct-use geothermal projects in Perth.